2011
DOI: 10.1007/s10464-010-9409-7
|View full text |Cite
|
Sign up to set email alerts
|

Mobilizing Communities to Implement Evidence‐Based Practices in Youth Violence Prevention: The State of the Art

Abstract: Community mobilization can increase the effective implementation of evidence-based practices (EBPs) in youth violence prevention. These strategies bring together people and organizations in a community to try to solve or reduce a problem. They help communities address the challenges of identifying EBPs, disseminating them to local decision-makers, and then implementing and sustaining them if they are successful. Science-based systems for implementing EBPs such as PROSPER and Communities That Care can help to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 33 publications
0
29
0
1
Order By: Relevance
“…Our review of the literature highlights two core challenges we must address to achieve population impact through EBIs (Backer and Guerra 2011; Durlak and DuPre 2008; Fixsen et al 2005; Glasgow et al 2006; National Research Council and Institute of Medicine 2009a; Proctor et al 2009; Spoth et al 2008; Westfall et al 2007). The first core challenge is to build infrastructures and the capacity for broad translation of evidence-based preventive interventions into community practices through prevention delivery systems.…”
Section: Addressing Core Challenges: An Integrated Conceptual Frameworkmentioning
confidence: 99%
“…Our review of the literature highlights two core challenges we must address to achieve population impact through EBIs (Backer and Guerra 2011; Durlak and DuPre 2008; Fixsen et al 2005; Glasgow et al 2006; National Research Council and Institute of Medicine 2009a; Proctor et al 2009; Spoth et al 2008; Westfall et al 2007). The first core challenge is to build infrastructures and the capacity for broad translation of evidence-based preventive interventions into community practices through prevention delivery systems.…”
Section: Addressing Core Challenges: An Integrated Conceptual Frameworkmentioning
confidence: 99%
“…At present, tested and effective preventive interventions to reduce youth violence reach only a small percentage of the population that could benefit from them (Backer and Guerra 2011). This special issue addresses a promising solution, namely, “community action among people and organizations in a community directed toward solving or reducing a problem” (Backer and Guerra 2011).…”
Section: Introductionmentioning
confidence: 99%
“…To address this problem, further research has been recommended on: (1) effective strategies to better translate proven interventions into practice; (2) technical assistance and other supports for practitioners implementing evidence-based interventions; and (3) delivery systems for evidence-based interventions (Backer & Guerra, 2011; Spoth & Greenberg, 2011). …”
mentioning
confidence: 99%
“…Yet, there are very limited data from randomized controlled studies on the efficacy of community partnership systems designed to deliver universal evidence-based interventions, particularly ones intended to reduce aggression and other conduct problem behaviors (Backer & Guerra, 2011; Hawkins et al, 2012; Spoth & Greenberg, 2011). An earlier study demonstrated that one such system, Communities That Care, was effective in reducing youth problem behaviors (Hawkins et al, 2012).…”
mentioning
confidence: 99%